Blockholder Ownership and Market Liquidity - Heflin, Frank; Shaw, Kenneth W. (Journal of Financial and Quantitative Analysis, 2000)
This paper examines the association between block ownership and market liquidity. Blockholders are believed to have access to private, value-relevant information via their roles as monitors of firms' operations. consistent with this, we find that firms with greater blockholder ownership, either by managers or external entities, have larger quoted spreads, effective spreads, adverse selection spread components, and smaller quoted depths.